Nicotine replacement therapy for smoking cessation. - Silagy, C; Mant, D; Fowler, G; Lancaster, T (2000)
BACKGROUND: The aim of nicotine replacement therapy (NRT) is to replace nicotine from cigarettes. This reduces withdrawal symptoms associated with smoking cessation to help resist the urge to smoke cigarettes. OBJECTIVES: The aims of this review were to determine the effectiveness of the different forms of nicotine replacement therapy (chewing gum, transdermal patches, nasal spray, inhalers and tablets) in achieving abstinence from cigarettes; to determine whether the effect is influenced by the clinical setting in which the smoker is recruited and treated, the dosage and form of the NRT used, or the intensity of additional advice and support offered to the smoker; and to determine whether combinations of NRT are more effective than one type alone. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group trials register. SELECTION CRITERIA: Randomized trials in which NRT was compared to placebo or no treatment, or where different doses of NRT were compared. We excluded trials which did not report cessation rates, and those with follow-up of less than six months. DATA COLLECTION AND ANALYSIS: We extracted data in duplicate on the type of subjects, the dose and duration and form of nicotine therapy, the outcome measures, method of randomisation, and completeness of follow-up. The main outcome measure was abstinence from smoking after at least six months of follow-up. We used the most rigorous definition of abstinence for each trial, and biochemically validated rates if available. Where appropriate, we performed meta-analysis using a fixed effects model. MAIN RESULTS: We identified 49 trials of nicotine gum, 32 of transdermal nicotine patch, four of intranasal nicotine spray, four of inhaled nicotine and two of nicotine sublingual tablet. Three trials compared combinations of two forms of nicotine therapy with one form alone. The odds ratio for abstinence with NRT compared to control was 1.72 (95% confidence interval 1.60 to 1.84), The odds ratios for the different forms of NRT were 1.63 for gum, 1.77 for patches, 2.27 for nasal spray, 2.08 for inhaled nicotine and 1.73 for nicotine sublingual tablet. These odds were largely independent of the intensity of additional support provided or the setting in which the NRT was offered. Eight weeks of patch therapy was as effective as longer courses and there was no evidence that tapered therapy was better than abrupt withdrawal. Wearing the patch only during waking hours (16 hours/day) was as effective as wearing it for 24 hours/day. The odds ratio for abstinence in the trials which directly compared 4 mg versus 2 mg gum in highly dependent smokers found a significant benefit in favour of 4 mg gum (odds ratio 2.67, 95% confidence interval 1.69 to 4.22). There is no strong evidence that combinations of forms of NRT are more effective. Only one study directly compared NRT against another pharmacotherapy (bupropion) and found that the latter was significantly more effective either alone or used in combination with nicotine patch than if nicotine patch was used alone. REVIEWER'S CONCLUSIONS: All of the commercially available forms of NRT (nicotine gum, transdermal patch, and in some countries, the nicotine nasal spray, nicotine inhaler and nicotine sublingual tablets) are effective as part of a strategy to promote smoking cessation. They increase quit rates approximately 1.5 to 2 fold regardless of setting. The effectiveness of NRT appears to be largely independent of the intensity of additional support provided to the smoker. Since all the trials of NRT reported so far have included at least some form of brief advice to the smoker, this represents the minimum which should be offered in order to ensure its effectiveness. Provision of more intense levels of support, although beneficial in facilitating the likelihood of quitting, is not essential to the success of NRT. There is promising evidence that bupropion may be more effective than NRT (either alone or in combination). (ABSTRACT